SYSTEM ADMINISTRATION OUTPATIENT CLINIC IN MEDIROS USING MICROSOFT VISUAL BASIC 6.0 AND MICROSOFT ACCESS - Hartati Tri Susilo; Don Elsyafitra., SKom. (Jurnal Sistem Informasi, 2009)
The development of increasingly advanced technology, especially computers, havenow entered a wide range of existing activity areas. The advantage of using computertechnology is characterized by speed, precision, and accuracy, as well as ensuring thatdata will be stored.The author conducted a study on administrative systems in use at the Clinic Mediros,wherein the data processing still using manual systems. This system has thedisadvantage of consuming much time and energy so as not effective.From these circumstances, the authors intend to provide an alternative in dataprocessing of patients, physicians, and medical treatment, but no longer manuallycomputerized order administrator in performing his job easier and also speed upservice to patients after medical examination.Storage of all data related to the administration system is stored in a database that iswell designed so that it can provide the necessary information quickly.